Van der Woude syndrome: Presentation of child with duodenal atresia with an interferon regulatory factor 6 variant - Helen Livesey; Uchechika Iroegbu; Meena Balasubramanian (Wolters Kluwer Medknow Publications, 2022)
Orofacial clefts are common birth defects and Van der Woude syndrome (VWS) is the most common form of orofacial cleft syndrome, accounting for approximately 2% of patients with a cleft.[1],[2] The cardinal features of VWS are lower lip pits associated with cleft lip and/or palate.[2],[3],[4] Lip pits are reported to occur in over 80% of individuals with VWS.[2] Most reported cases of VWS have been linked to chromosome 1q32-q41.[5],[6],[7] The interferon regulatory factor 6 (IRF6) gene, which is located at 1q32-p41 region, has been implicated in several studies.[2],[8] There are over 300 IRF6 variants that have been identified in patients with VWS, with approximately 50% of these being missense variants.[9] This paper describes a 7.5-year-old male patient that is heterozygous for a missense variant in C.101A >C p.(Lys34Thr) which is likely to be pathogenic.[9] This patient has the cardinal features for VWS but also has duodenal atresia. Neither the truncating variant identified in this patient nor other variants associated with VWS have been previously linked to duodenal atresia.